Penyelesaian Perselisihan Hubungan Industrial Menurut Undang-Undang Ketenagakerjaan - I Ketut Simpen; Herry Indiyah Wismani (Universitas Mahendradatta, 2019)
Disputes or disputes are always possible in every human relationship including disputes inwork relations. Industrial relations disputes usually occur between workers / employers and employersor between workers 'organizations / labor organizations and company organizations / employers'organizations. Industrial relations disputes can be divided into two, namely: a) Industrial relationsdisputes according to their nature, which consist of: Collective industrial relations disputes, andindividual industrial relations disputes b) Industrial Relations Disputes according to their type, whichconsist of Rights Disputes and Interest Disputes. This research is a normative legal research that is astudy that mainly analyzes the provisions of positive law and the principles of law, by carrying outsystematic explanations. The problems studied are how is the Industrial Relations Dispute ResolutionMechanism according to the Labor Law. The industrial relations dispute resolution mechanism iscarried out in two ways, namely through a non-litigation path that is carried out by bipartid (eachdisputing party) and tripartid (mediation, negotiation, and consolidation) and through litigationchannels (court lines namely Industrial Relations Control.